Different bacterial communities in heat and gamma irradiation treated replant disease soils revealed by 16S rRNA gene analysis – contribution to improved aboveground apple plant growth? - Yim, Bunlong; Winkelmann, Traud; Ding, Guo-Chun; Smalla, Kornelia (Frontiers in Microbiology, 2015)
Replant disease (RD) severely affects apple production in propagation tree nurseries and in fruit orchards worldwide. This study aimed to investigate the effects of soil disinfection treatments on plant growth and health in a biotest in two different RD soil types under greenhouse conditions and to link the plant growth status with the bacterial community composition at the time of plant sampling. In the biotest performed we observed that the aboveground growth of apple rootstock M26 plants after eight weeks was improved in the two RD soils either treated at 50 °C or with gamma irradiation compared to the untreated RD soils. Total community DNA was extracted from soil loosely adhering to the roots and quantitative real-time PCR revealed no pronounced differences in 16S rRNA gene copy numbers. 16S rRNA gene-based bacterial community analysis by denaturing gradient gel electrophoresis (DGGE) and 454-pyrosequencing revealed significant differences in the bacterial community composition even after eight weeks of plant growth. In both soils, the treatments affected different phyla but only the relative abundance of Acidobacteria was reduced by both treatments. The genera Streptomyces, Bacillus, Paenibacillus and Sphingomonas had a higher relative abundance in both heat treated soils, whereas the relative abundance of Mucilaginibacter, Devosia and Rhodanobacter was increased in the gamma-irradiated soils and only the genus Phenylobacterium was increased in both treatments. The increased abundance of genera with potentially beneficial bacteria, i.e. potential degraders of phenolic compounds might have contributed to the improved plant growth in both treatments.